EKSPERIMEN DAN PEMODELAN NUMERIK ALIRAN DAN REAKSI KIMIA TURBULEN PADA TABRAKAN DUA JET BERHADAPAN - Mulyana, Achmad
Abstract: Experimental flow visualization acid-alkali physical modeling and numerical model using turbulence a kinetic energy-dissipation (k-c) model and a Reynolds Stress Model (RSM) have been performed to study phenomenon of flow pattern and concentration distribution an impinging two-opposed-jet in a cross flow. For acid-alkali model, jet and main stream fluids were established experimentally using 0,025 M NaOH solution and 0.00925 M HCI solution. Measurements of jet trajectory, mixing length and acid concentrations (pH) were performed. Parametric variations for characterizing the mixing process were examined and correlated resulting model equations. Results show that curvature gradient of jet trajectories increase as momentum flux ratio (RG) increase. The minimum mixing length indicating optimal mixing condition persists over a range of RG 122-181 at nozzle diameter (D) = 2 nun, 16-18 at D = 4 mm, and 4-5 at D = 6 mm. The mixing process occurs much more effectively as the ratio of nozzle to main pipe diameter (D/H) is reduced. Acid concentration (pH) distribution shows symmetrical behavior at the main pipe mid-height point (Y/H = 0.5) and decrease along vertical distance (Y/H). The minimum pH along the vertical distance occurs at the main pipe mid-height point (Y/H = 0.5). This means that the acid-base reaction dominantly occurs around the mid-height point (Y/H = 0,5). The RG values influence pH values but not the profile along both radial stream and axial stream. Computed results with both turbulence models are compared to experimental data for impinging two-opposed-jet in a cross flow without chemical reaction. Both models yield reasonable agreement for the mean flow velocity. However, both models give significant discrepancies in turbulent quantities. The overall results show that the RSM turbulent model did not give the significant improvement of the prediction. Computed results with both turbulence models for impinging twoopposed-jet in a cross flow with chemical reaction show that the minimum mixing length persists over a RG 181 at nozzle diameter (D) = 2 mm, 18.3 at D = 4 mm, and 4.6 at D = 6 mm. At nozzle diameter = 4 mm with RG = 183 yields the mixing zone most effectively.